Evaluation of the Effect of Different Doses of X-Ray Irradiation on the Physicochemical and Microbiological Profiles of Liberica Green Coffee Beans - Khairunnisa, Meutia Irdina; Kartika, Annisa Aurora; Sunarharum, Wenny Bekti; Mahatmanto, Tunjung (Directorate of Research and Community Services, 2024)
Liberica coffee has significant potential for cultivation and trade in Indonesia. The coffee trade requires effective post-harvest processing to maintain commodity quality. X-ray irradiation offers several advantages as a post-harvest processing method. However, research on X-ray irradiation remains limited. This study was designed to determine the effect of different doses of X-ray irradiation on the microbiological and physicochemical characteristics of Liberica green coffee beans and to identify the optimal dose for treatment. The research employed a randomized block design (RBD) method with five different doses of X-ray irradiation: 0 kGy, 2.7 kGy, 5.4 kGy, 7.2 kGy, and 10.8 kGy. The results indicated that varying doses of X-ray irradiation had no discernible effect on the color, water, protein, and fat content of Liberica green coffee beans. However, differences in the X-ray irradiation dose significantly affected the degree of acidity (pH), caffeine content, total sugar, antioxidants, and phenol levels in the beans. Additionally, there was a decrease in the Total Plate Count (TPC) with increasing doses of X-ray irradiation. The best treatment achieved was at an irradiation dose of 7.2 kGy.